Characterisation and dissolution kinetics of tamarind and pineapple tablets - Mokhtar, Taufiq Aminullah (2015)
Fruits in fresh form have limited shelf life and often face difficulty during handling and preparation therefore tabletting is one of the best alternative for the fruit juice. This research done due to the lack of research in the area of tamarind and pineapple tablet characterisation and dissolution kinetics. Its dissolution properties are important as it depends on the process of tablets dissolve in distill water, simulated gastric juice of pH1.2 and simulated intestinal juice of pH 6.8 which has been used in this study. Both of the fruits went spray drying process. The powders were then compressed into tablets using a cylindrical uniaxial die. Pressures of up to 22.28 MPa were applied to the die via a universal testing machine. The nutritional value in terms of crude protein (0.33% - 0.60%), moisture content (4.8% - 25.31%), crude fiber (16.92% - 79.92%), and fat (0.40% - 0.63%) for both fruits pulp and powders showed significant differences in values with p<0.05. The vitamin C release was analyzed using 2,4-dinitrophenyl hydrazine (DNPH) method. In-vitro dissolution study of the fruit tablet were been analysed by four established release kinetics model equations. The best fit mathematical model for the tamarind and pineapple fruit tablets were determined based on the coefficient of correlation ‘R2’ values. A microbial stability test was done to calculate the colony forming units (CFU/g) of both tamarind and pineapple fruit powder tablets. The shelf life of pineapple tablet is 14 days and tamarind tablet is 21 days, which were in the acceptable value range of colonies for fruits as it were less than 10000 CFU/ml following the United States Food and Drug Administration (FDA). These findings indicate that it is important to compact fruit powder into tablet because fruit powder in tablet form is easy to dissolve and may provide an excellent alternative for healthy beverage consumption and a creative product development and as an approach to meet consumer’s demand.